Enhancing Diabetes Care: Strategies for Preventing Inpatient Hypoglycemia - Jacob, Rosmin; Biju, Blessy; Panayappan, Dr. L.; Kumar Sharma, Dr. Rajesh (Asian Journal of Pharmaceutical Research and Development, 2024)
Hypoglycemia, a common complication of diabetes treatments among hospitalized patients, poses significant risks, including increased morbidity, longer hospital stays, higher readmission rates, and greater financial burdens. In the hospital setting, hypoglycemia poses a significant challenge, impacting patient health and healthcare resources. This review dives deep into this issue, shedding light on the many factors contributing to hypoglycemia during hospital stays and its effects on patients. It emphasizes practical strategies for preventing hypoglycemia, such as patient education and the use of new technologies like continuous glucose monitoring. Additionally, it highlights the crucial role pharmacists play in managing hypoglycemia and improving patient care. By offering clear insights and actionable recommendations, this review aims to help healthcare providers better navigate the complexities of inpatient diabetes care for improved patient outcomes.